Efektivitas Peningkatan Kinerja Aparatur Sipil Negara Melalui Sistem Merit (Meryt System) Pada Sekretariat Daerah Kabupaten Bener Meriah Tahun 2019 - Kusmana, Didi; -, Zulham; Abubakar, Muhammad Bin (Jurnal Transparansi Publik (JTP), 2022)
The Regional Secretariat of the Bener Meriah Regency in 2019 is the location of this study, which explores the efficacy of raising state public servants' performance using the merit system. The goal of the study is to comprehend how the spoil system can impede efforts to increase ASN performance as well as the efficacy of enhancing ASN performance through the merit system. Hani Handoko's theory of effectiveness, which uses outcome indicators (results) from the execution of programs/activities, is the theoretical framework that is applied. A qualitative research method was adopted for the study. The findings revealed that improving the performance of ASN through the Merit System at the Bener Meriah Secretariat in 2019 was still ineffective due to the low quality of the ASN serving in the Bener Meriah Secretariat due to the influence of the spoil system implementation due to the element of closeness or kinship with political officials in the area. Regency Bener Meriah The spoil system has a significant impact and hinders the effectiveness of improving the performance of ASN in the Bener Meriah Secretariat in 2019, because if the spoil system is still used in the placement and recruitment of ASN placed in the Setdakab, it will have an impact on the performance of other ASN, because the roles of ASN are different because ASN roles that are placed based on ability and competence qualifications will be defeated by ASN that is dominated by a spoil system because it is based on political power or through political intervention and power.